Вплив глюкози на структуру хрящової тканини: фізичний механізм - Zabashta, Yu.F.; Vergun, L.Yu.; Alekseev, O.M.; Svechnikova, O.S.; Lazarenko, M.M.; Bulavin, L.A. (Publishing house "Academperiodika", 2025)
We propose a mechanism according to which the introduction of glucose into cartilage tissue changes the structure of this tissue. Cartilage tissue is considered to be a porous medium, where the role of solid component is played by collagen fibers and layers where proteoglycans are located. Collagen chains that connect the aforementioned objects are adsorbed on the surface of the fibers and the layer. The thermodynamic features of the links of adsorbed chains have been determined. It was shown that glucose molecules, being introduced into cartilage tissue, partially displace the adsorbed chains from the fiber surface. These chains cover cracks that may appear in the fiber under the action of external loads, which leads to a reduced rigidity of proteoglycan layers. A conclusion has been drawn that the introduction of glucose molecules enlarges the shear compliance of cartilage tissue. This conclusion is confirmed by experimental results obtained for a model system, gelatin gel, whose structure is considered to be similar to that of cartilage tissue.